2021
DOI: 10.1177/02654075211012098
|View full text |Cite|
|
Sign up to set email alerts
|

Examining associations between COVID-19 stressors, intimate partner violence, health, and health behaviors

Abstract: The economic, social, and health impacts of the COVID-19 pandemic are expected to increase the occurrence of intimate partner violence (IPV) victimization. IPV victimization may, in turn, contribute to physical and mental health, substance use, and social distancing behaviors during the COVID-19 pandemic. The primary objective of the current study was to understand the extent to which 1) COVID-19 stressors are associated with IPV victimization and 2) IPV victimization is associated with health and health behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 53 publications
4
39
0
1
Order By: Relevance
“…As an example, Gosangi et al ( 2021 ) noted a decline in the number of patients seeking healthcare for IPV-related injuries but of those that sought care, the severity of injuries was greater during the pandemic compared with previous years. Similarly, a study by Gresham et al ( 2021 ) noted associations between increased COVID-19 stressors and physical IPV victimization.…”
Section: Introductionmentioning
confidence: 78%
“…As an example, Gosangi et al ( 2021 ) noted a decline in the number of patients seeking healthcare for IPV-related injuries but of those that sought care, the severity of injuries was greater during the pandemic compared with previous years. Similarly, a study by Gresham et al ( 2021 ) noted associations between increased COVID-19 stressors and physical IPV victimization.…”
Section: Introductionmentioning
confidence: 78%
“…We use Karney and Bradbury’s (1995) vulnerability-stress-adaptation (VSA) model as adapted by Pietromonaco and Overall (2021) to the COVID-19 context to further categorize and understand these themes. This model has been successfully used in multiple COVID-19 and close relationship studies that were ultimately included here (e.g., Fleming & Franzese, 2021 ; Gresham et al, 2021 ; Holmberg et al, 2021 ; Vowels et al, 2021 ). Using family and relationship theory, this adapted VSA model proposes that (1) external stress (such as COVID-19 and its attendant regulations, change in job status, isolation, etc.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…Previous research has shown that alcohol consumption is associated with feelings of behavioral and mental disengagement, indicating that alcohol-related coping is generally ineffective and could further exacerbate the risk for engaging in intimate partner violence [ 28 , 29 ]. Links among COVID-19 stressors, IPV victimization, substance use, and quarantine behaviors are emerging [ 30 ]. Additionally, alcohol consumption is financially costly, and, when consumed in excess, is associated with many other negative physical health and disease processes.…”
Section: Discussionmentioning
confidence: 99%